Offline queries in software defined networks - Zhang, Hui; Arzani, Behnaz; Ivancic, Franjo; Rhee, Junghwan; Arora, Nipun; Jiang, Guofei (2017)
Offline queries in software defined networks Hui Zhang, Behnaz Arzani, Franjo Ivancic, Junghwan Rhee, Nipun Arora, Guofei Jiang Methods and systems for finding a packet's routing path in a network includes intercepting control messages sent by a controller to one or more switches in a software defined network (SDN). A state of the SDN at a requested time is emulated and one or more possible routing paths through the emulated SDN is identified by replaying the intercepted control messages to one or more emulated switches in the emulated SDN. The one or more possible routing paths correspond to a requested packet injected into the SDN at the requested time.
Patent office US